Evaluation of Enzymatic Removal of Cooling Water System Biofilm Using its Own Producer Bacteria - Ceyhan, N. (Asian Journal of Chemistry, 2012)
Biofilms can cause corrosion and seriously affect flow, pressure drop and the efficiency of heat transfer from metal surfaces. Cooling water systems, are essential parts in many industries, provide ideal aquatic environments for the microbiological fouling caused by biofilms. In these systems, the protection of bacteria by exopolysaccharide matrix construction in biofilm, bacterial resistance to biocides and their negative environmental effects are the main reasons to search alternative biofilm removal strategies. In this study, it was investigated that removal of cooling water system-biofilm through its own producer bacteria enzymatically. For this aim, 4 supernatant from biofilm bacteria, cultured onto polysaccharide substrates, were investigated for their enzymatic properties and their ability to remove a biofilm made with the same 4 bacteria. In conclusion, the best biofilm removal activities were obtained in gellan gum (91 ± 2 %) and alginate (62 ± 3 %) with Sphingomonas paucimobilissupernatant, xanthan gum (88 ± 6 %) and xylan (70 ± 4 %) with Bacillus sp. supernatant, alginate (75 ± 5 %), gellan gum (25 ± 3 %) and xylan (14 ± 3 %) with Pseudomonas fluorescens supernatant, gellan gum (45 ± 7 %) and xylan (36 ± 5 %) with Aeromonas caviae supernatant. This study is interesting in aspect that the own producer enzymes may dislodge biofilm by degrading the exopolysaccharide matrix and data showed that the biofilm was removed by its own producers via polysaccharases to attack to various polysaccharide substrates, for control and disinfection practices of cooling water systems.